SAT0123 RISK FOR TUBERCULOSIS DURING TREATMENT WITH BIOLOGICAL THERAPY: IS IT TIME FOR REVIEWING SCREENING PROTOCOL? – RESULTS FROM BRAZILIAN REGISTRY OF BIOLOGICAL THERAPIES IN RHEUMATIC DISEASES (BIOBADABRASIL). (June 2019) - Medeiros, Ana; Bredemeier, M; Valim, V; Pinheiro, M; Macieira, C; Duarte, A; Stadler, B; Ranza, R; Bertolo, M; Miranda, J; Brenol, C; Castro, G; et al.
Abstract : Background: As Brazil is accountable for 33% of the tuberculosis (TB) burden in Americas, with an annual incidence of 33.5/100, 000 in 2017[1], the occurrence of tuberculosis infection in patients with rheumatic diseases in use of biological therapy is a recurrent concern. Objectives: To assess incident TB among patients with rheumatic disease in use of biological therapy in a country with high incidence of TB. Methods: BiobadaBrasil is a multicentric prospective cohort study involving patients with rheumatic diseases who started the first biologic or a synthetic disease modifying anti-rheumatic drug (DMARD)[6]. This analysis includes patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS) recruited from Jan 2009 to Aug 2018 and followed-up for one or multiple courses of treatment until censoring or incident TB. The primary outcome was the incidence of tuberculosis (in any organ site). The history of exposure to tuberculosis, chest Rx, screening and treatment for latent tuberculosis infection (LBTI), and use of prophylactic isoniazid were evaluated before each course of treatment. Multivariate Cox proportional hazards models (with DMARDs included as time-varying covariates) were used to estimate hazard ratios (HR) and 95% confidence intervals (CI); analyses were performed with the Survival package of R. Results: Sample: 2858 patients (female =70, 2%; RA = 72%, AS=20%, and PsA = 8%). A total of 31 (1.1%) patients developed tuberculosis during treatment. One patient on abatacept and one on tocilizumab developed TB while all the others were on TNF-inhibitors(29). The median (interquartile range) exposure to the current DAMRD course was 11.1 (5.9-20) months. TB patients did not significantly differ from others regarding disease duration, sex or age. Almost half (n=14, 45%) of TB patients did not present evidence of previous exposure or any screening positive test for TB; 9 (29%) TB patients had received adequate LTBI treatment (isoniazid) recently or in the past. Furthermore, 8(26%) had incomplete/inconsistent screening. The overall incidence of TB was 1.9/1000 patients/year, and was not significantly different among the diseases (1.63 for RA, 2.06, for AS, and 3.79/1000/year for PsA). In univariate analysis, exposure to anti-TNF monoclonal antibodies (HR 3.1, 95%CI 1.18-8.15, P=0.02) and presence of any marker of previous contact with TB (positive history of TB, known contact with TB, positive TST, or abnormal chest X-ray: HR 4.2 (2.1-8.5, p<0, 001) were positively associated with the risk of TB. Including simultaneously these variables in the Cox model, they were independent risk factor for TB (p<0.05). Conclusion: Monoclonal anti-TNF antibodies and previous exposure/diagnosis of TB are independent risk factors for developing TB in Brazil. TB cases occurred both early and lately during treatment courses, suggesting LTBI screening failures, treatment non-adherence or re-exposure. Current application and content of the protocol for screening and treatment of LTBI needs to be reviewed. References: [1] WHO TB report2018.https://www.who.int/tb/publications/global_report/en/ [2] Rev Bras Reumatol Engl Ed. 2017;57Suppl 2:477-483. doi: 10.1016/j.rbre.2017.05.005. Acknowledgement: monitor P Cabral, MDs N Sacilotto, H Pereira, F Sztajnbok. Disclosure of Interests: Ana Medeiros: None declared, M Bredemeier: None declared, V Valim: None declared, M Pinheiro Consultant for: Janssen, Pfizer, Speakers bureau: Abbot, Janssen, Novartis, C Macieira: None declared, A Duarte: None declared, B Stadler: None declared, R Ranza: None declared, M Bertolo: None declared, J Miranda Speakers bureau: Pfizer, C Brenol Speakers bureau: Pfizer, Roche, Janssen, Bristol., G Castro: None declared, V Fernandes Speakers bureau: Janssen, D Titton: None declared, F Sauma: None declared, I Pereira: None declared, R Botelho: None declared, H Carvalho: None declared, A Hayata: None declared, P Louzada: None declared, A Ranzolin: None declared, S Studart: None declared, G Castelar: None declared, A Kakehasi Grant/research support from: Abbvie, UCB, JANSSEN, ROCHE, NOVARTIS, PFIZER, Consultant for: Abbvie, UCB, JANSSEN, ROCHE, NOVARTIS, PFIZER, Paid instructor for: JANSSEN, Speakers bureau: Abbvie, UCB, JANSSEN, ROCHE, NOVARTIS, PFIZER, W Bianchi: None declared, R Acayaba: None declared, I Silveira: None declared, H Resende: None declared, J Amaral: None declared, L Rocha: None declared, M Gazzeta: None declared, L Carvalho: None declared, S Schowalski: None declared, D Feldman: None declared, I Laurindo Consultant for: Abbvie, UCB, GSK, JANSSEN, LILLY, NOVARTIS, PFIZER, Paid instructor for: Abbvie, JANSSEN, Speakers bureau: Abbvie, UCB, GSK, JANSSEN, LILLY, NOVARTIS, PFIZER, ROCHE, J Provenza: None declared